Antibacterial spirooxindole alkaloids from Penicillium brefeldianum inhibit dimorphism of pathogenic smut fungi - Shi, Huajun; Jiang, Jinyan; Zhang, Hang; Jiang, Haimei; Su, Zijie; Liu, Dandan; Jie, Ligang; He, Fei (Frontiers in Microbiology, 2022)
Three new antibacterial spirooxindole alkaloids, spirobrefeldins A–C (1–3), together with four known analogs, spirotryprostatin M (4), spirotryprostatin G (5), 12β-hydroxyverruculogen TR-2 (6), and 12α-hydroxyverruculogen TR-2 (7), were isolated from terrestrial fungus Penicillium brefeldianum. All the new compounds were elucidated extensively by the interpretation of their NMR (1D and 2D) spectra and high-resolution mass data, and their absolute configurations were determined by computational chemistry and CD spectra. The absolute configurations of spiro carbon C-2 in spirotryprostatin G (5) and spirotryprostatin C in literature were reported as S, which were revised to R based on experimental and calculated CD spectra. All the compounds were evaluated for their antimicrobial activities toward Pseudomonas aeruginosa PAO1, Dickeya zeae EC1, Staphylococcus epidermidis, Escherichia coli, and Sporisorium scitamineum. Compound 7 displayed moderate inhibitory activity toward dimorphic switch of pathogenic smut fungi Sporisorium scitamineum at 25 μM. Compounds 3 and 6 showed weak antibacterial activities against phytopathogenic bacterial Dickeya zeae EC1 at 100 μM.